SOCIOLECT AND DIALECT VARIATIONS OF THE JAVANESE LANGUAGE IN BOJONEGORO - Rina Amalia; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This paper discusses the sociolect and dialect variations of the Javanese language in Bojonegoro. With the methods of observation, interviews, and notes, the results of the research show that sociolect is a variation of language based on social groups while dialect is a variation of language based on the area of ????language community. There is a sociolect phenomenon in Bojonegoro, especially in Bumirejo Village, namely the use of sociolects which varies based on age, intellectual, and occupational social groups. The dialect phenomenon in Bojonegoro, especially in the villages of Bumirejo, Sugihwaras, Sumberwangi, Sumuragung, and Cangakan, is the use of variations of 1 lexeme that is different in terms of phonology and variations of 13 different lexemes in terms of lexical in the five villages. Keywords: sociolect, dialect, Javanese, Bojonegoro